Direct Monitoring Reveals Initiation of Turbidity Currents From Extremely Dilute River Plumes. Issue 20 (29th October 2019) - Hage, Sophie; Cartigny, Matthieu J.B.; Sumner, Esther J.; Clare, Michael A.; Hughes Clarke, John E.; Talling, Peter J.; Lintern, D. Gwyn; Simmons, Stephen M.; Silva Jacinto, Ricardo; Vellinga, Age J.; Allin, Joshua R.; Azpiroz‐Zabala, Maria; et al.
Abstract: Rivers (on land) and turbidity currents (in the ocean) are the most important sediment transport processes on Earth. Yet how rivers generate turbidity currents as they enter the coastal ocean remains poorly understood. The current paradigm, based on laboratory experiments, is that turbidity currents are triggered when river plumes exceed a threshold sediment concentration of 1 kg/m 3 . Here we present direct observations of an exceptionally dilute river plume, with sediment concentrations 1 order of magnitude below this threshold (0.07 kg/m 3 ), which generated a fast (1.5 m/s), erosive, short‐lived (6 min) turbidity current. However, no turbidity current occurred during subsequent river plumes. We infer that turbidity currents are generated when fine sediment, accumulating in a tidal turbidity maximum, is released during spring tide. This means that very dilute river plumes can generate turbidity currents more frequently and in a wider range of locations than previously thought. Key Points: Here we document for the first time how very dilute (up to 0.07 kg/m 3 ) river plumes can generate powerful turbidity currents Such low sediment concentrations are 20 times lower than those predicted by past theory and experiments Therefore, turbidity currents are likely to be much more frequent and occur at a far wider range of locations than previously thought